Photodissociation Mechanism Study of 1, 3-Dibromopropane using Theoretical Calculations - Roaa A-Hussien; Abbas A-Ali Drea (Al-Qadisiyah Journal of Pure Science, 2018)
A simulation study has been conducted by using Quantum calculation methods like DFT, Ab-initio and semiempirical methods to estimate the photolysis mechanism for 1,3-dibromopropane in the gas phase and its effect on the ozone layer.Energetic properties have been calculated like total energy and thermodynamic functions (G, S, Hf) for all chemical species thatâ€™s participate in the suggested reaction mechanism. Geometry optimized and single point calculation has been done to understand the configuration interaction singly excited state for three different conformations of 1, 3-dibromopropane which is found that the C2 isomer is the most stable with total energy being equal to -26652.031 kCal mol-1. Molecular orbital and their energy gap has been calculated using Ab initio//6-311G* and Beak 88 LYP//3-21G(d) level.  The cleavage occurs at a wavelength equal to 442.571 nm and yields the 3-bromopropyl and bromine radical with activation energy equal to 98.624 kCal mol-1 calculated by using MNDO/d method. The 3-bromopropyl radical undergoing secondary dissociation through second C-Br bond to give the cyclopropane molecule as a final product with an energy barrier equal to 68.83 kCal mol-1.